2015
DOI: 10.1007/s10554-015-0768-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance analysis versus lung ultrasonography for optimal risk prediction in hemodialysis patients

Abstract: Fluid overload is associated with adverse outcomes in hemodialysis (HD) patients. Two bedside methods are increasingly utilized to evaluate objectively fluid status-bioimpedance and lung ultrasonography, but there is no available direct, head-to-head comparison of their prognostic significance. Importantly, their predictive abilities have never been tested in a HD population, alongside those of a classic model that also incorporates established echocardiographic parameters of increased mortality risk. Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
2
36
1
Order By: Relevance
“…The presence of pulmonary B lines in patients undergoing chronic hemodialysis has been previously associated with an increase in mortality [19-21]. As a marker of both fluid status and heart function, this technique provides important information on fluid status and could be useful to individualize fluid removal during dialysis, especially in patients with cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of pulmonary B lines in patients undergoing chronic hemodialysis has been previously associated with an increase in mortality [19-21]. As a marker of both fluid status and heart function, this technique provides important information on fluid status and could be useful to individualize fluid removal during dialysis, especially in patients with cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The B-line score has a significant discriminating power for 1 year survival unlike overhydration measured by whole body bioimpedance [20]. However, the B-line score did not improve mortality prediction over a baseline model incorporating left ventricular mass index suggesting that the observed increase in mortality is related to cardiac function [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Zoccali et al [6] first showed that the degree of lung congestion was a better predictor for mortality, cardiovascular events, and hospitalization than the assessment done by the NYHA score, and that it could even improve prediction for mortality but not cardiovascular events. Later, these results were confirmed by Siriopol et al [75], which showed that lung US was associated with prediction of survival even after the adjustments for echocardiographic and bioimpedance parameters, whereas this technique is not able to improve risk prediction for all-cause mortality in hemodialysis patients beyond classical and echocardiographicbased risk prediction scores/parameters [76].…”
Section: Lung Ultrasonographymentioning
confidence: 91%
“…On the other hand, in an older study, the same group had found that risk prediction for death by assessing fluid status was improved only by using BIA but not by using LUS [76]. Although the majority of the previous observational studies showed a reduction in mortality in ESRD patients, in a recent metaanalysis that included only randomized controlled trials, BIA was not associated with a significant improvement in survival, showing only a better BP control [25].…”
Section: Bioimpedancementioning
confidence: 97%
“…Bioimpedance allows quantification of excess extracellular volume by comparison with a healthy population. This safe and noninvasive method can be used to determine hydration status in patients on dialysis therapy, and different from other methods allows the quantification of intracellular and extracellular volumes [6,10,11]. However, this approach is time-consuming and difficult to handle in everyday practice.…”
Section: Introductionmentioning
confidence: 99%